PENGARUH MODEL PEMBELAJARAN STEM-PJBL TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA PADA MATERI PENCEMARAN LINGKUNGAN - Yasir Sukmawijaya; Suhendar Suhendar; Aa Juhanda (Department of Biology Education, Faculty of Education and Teacher Training, UIN Sunan Gunung Djati Bandung, 2019)
The purpose of this study was to determine the effect of STEM-based Project learning models on students' thinking abilities. Learning with this STEM-based project model needs to be applied and trained to students because it not only develops the ability to think creatively, but also other abilities and can be developed such as critical thinking skills, and ability to make decisions. The research method that be used is quasi-experiment with the design of Nonequivalent Control Group. This research was conducted at the Cikidang State High School 1 with the research population being class X. The sampling technique used was Purposing Sampling. The results showed that the experimental class N-gain value was 0.71 higher than the control class of 0.47. The z test results show that the data produced is in accordance with the criteria namely Zhitung = 8, 91> Ztable = 1,998, meaning that H0 is rejected and H1 is accepted, meaning that the learning model STEM-based project influences students' creative thinking skills in environmental pollution material. The responses from students to the STEM-based learning model provide positive responses to the implementation of learning activities.